The Legitimacy of Liberal Feminism in Preeti Shenoy’s Select Texts * - Pandeeswari, Dhanuskodi; Hariharasudan, Anandhan (Jordan Journal of Modern Languages & Literatures, 2022)
Postmodernism is a philosophical movement that comprises many perspectives. Feminism is a postmodern perspective and deals with all genders having equal rights and opportunities. Liberal feminism is one of the branches of feminism. Liberal feminism is concerned with women and their suffering, especially how they overcome all the impediments and make decisions independently. The aim of the study is to delve into the postmodern perspective of liberal feminism in Preeti Shenoy’s selected texts, The Secret Wish List (2012), Tea for Two and a Piece of Cake (2014) and It Happens for a Reason (2014). Preeti Shenoy is a famous Indian postmodern writer, and her contributions to liberal feminism cannot be denied. Liberal feminism is part of the feminist movement; it deals with women protagonists and their suffering. From those sufferings, they liberate and take all the decisions independently. Liberal feminism elucidates women empowerment. The precursors of liberal feminism and distinguished thinkers associated with the movement include Mary Wollstonecraft, John Stuart Mill, Susan Moller Okin, Martha Nussbaum and Zillah Eisenstein. The present study has adopted the elements of liberal feminism as presented in their works. The methodology of the study has adopted the concepts of liberal feminism such as moral theory, theory of justice, advocating educational and social equity for women, constructing a theory of capitalist patriarchy and socialist feminism, and capability approach. These theories substantiate the aspects of liberal feminism as manifested in Shenoy’s selected works. The results of the study are evaluated with other studies considering liberal feminism. Keywords: Liberal Feminism, Suffering, Empowerment, Patriarchy, Justice.